Placental growth factor and apoptosis as early prognostic factor of placental insufficiency - Filonenko, T. G.; Davydova, A. A.; Ermola, Yu. A.; Nechiporenko, V. V.; Shalanin, V. V.; Syurina, N. A.; Menshikova, O. P.; Kuzmin, M. N.; Fedotov, V. V.; Beketov, A. A. (Journal of Education, Health and Sport, 2015)
Filonenko T.G., Davydova A.A., Ermola Yu.A., Nechiporenko G.V., Shalanin V.V., Syurina N.A., Menshikova O.P., Kuzmin M.N., Fedotov V.V., Beketov A.A. Placental growth factor and apoptosis as early prognostic factor of placental insufficiency. Journal of Education, Health and Sport. 2015;5(1):69-74. ISSN 2391-8306. DOI: 10.5281/zenodo.13990 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%281%29%3A69-74 https://pbn.nauka.gov.pl/works/527851 http://dx.doi.org/10.5281/zenodo.13990 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2014. Revised 05.10.2014. Accepted: 25.12.2014. PLACENTAL GROWTH FACTOR AND APOPTOSIS AS EARLY PROGNOSTIC FACTOR OF PLACENTAL INSUFFICIENCY Filonenko T.G., Davydova A.A., Ermola Yu.A., Nechiporenko G.V., Shalanin V.V., Syurina N.A., Menshikova O.P., Kuzmin M.N., Fedotov V.V., Beketov A.A. Departement of pathomorphology. State Institution “Crimea State Medical University named after S.I. Georgievsky”, Simferopol, Crimea Republic, Russian Federation Summary Aim is to determine and measurement of placenta growth factor (PLGF), to demonstrate apoptosis in the human placenta in normal and abnormal pregnancies would usefully predict subsequent placental insufficiency. Clinico-functional evaluation of fetoplacental complex and definition of placental growth factor (PLGF) activity in serum of 55 pregnant women has been carried out. Histological verification of chronic placental insufficiency showed 3 types of patients: Compensatory chronic placental insufficiency, Subcompensatory and Subcompensatory with acute decompensation. Immunohistochemically a cross-sectional study was conducted to determine the expression of antybodies: marker of angiogenesis - CD34 , of apoptosis - P53 and antiapoptotic protein bcl2. Calculation of number of positive cells on 3-d visual areas of slide (200 magnification) took place. Comparing information of indexes of level of PLGF in the whey of blood, indexes of CD34 positive vessels and apoptosis it is possible to suppose that the investigated data show the dynamics of pathomorphologic changes in a placenta at chronic placenta insufficiency and can be diagnostic criteria. Key words: human placenta, abnormal pregnancies, angiogenesis, apoptosis.